FENOMENA KELAS PENARI WAYANG WONG DI YOGYAKARTA PADA MASA LAMPAU (1823—1855) - R.M. Momo Pramutomo (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2005)
This article discusses the phenomena of groups of dancers in Yogyakarta in the past (1823-1855). The discussion includes the aspects of social history. Particular reference is given to a Chinese capitan, Tan Jin Sing, who inspired the use of dancers as political satire within the sultan palace. This article presents a comprehensive study of dance history from different perspective. The dancer classes in the court of Yogyakarta Kraton can be recognized from one of the most influent phenomena in historical court dance in the Yogyakarta Palace.